Multilevel Health Promotion Strategies to Prevent Prediabetes Related to Sedentary Lifestyles in Adolescents: A Systematic Public Health Review - Yunus, Moch.; Andyastanti, Tisnalia Merdya; Fanani, Erianto (Indonesian Journal of Advanced Research, 2026)
A sedentary lifestyle among adolescents represents a major risk factor for the development of prediabetes and metabolic syndrome, which may affect long-term health outcomes. This condition highlights the importance of comprehensive and sustainable health promotion strategies. This study aims to systematically review health promotion strategies for preventing prediabetes associated with sedentary behavior among adolescents. This study employed a literature review method by analyzing ten selected primary research articles. The articles were screened based on topic relevance, study design, and their focus on health promotion and metabolic syndrome prevention. Data were analyzed using descriptive and thematic approaches to identify key intervention characteristics and outcomes. The findings indicate that multilevel interventions based on socio-ecological models are more effective than passive educational approaches. School-based, community-based, and digital health interventions were shown to increase physical activity levels and improve metabolic indicators. Moreover, habit-based interventions and targeted programs for high-risk groups demonstrated greater sustainability of health outcomes. In conclusion, integrative, adaptive, and multisectoral health promotion strategies are effective approaches for preventing prediabetes among adolescents with sedentary lifestyles.